Clinical Microbial Identification of Severe Oral Infections by MALDI-TOF Mass Spectrometry in Stockholm County: an 11-Year (2010 to 2020) Epidemiological Investigation - Khaled Al-Manei; Mahin Ghorbani; Sabrina Naud; Kholod Khalil Al-Manei; Michał J. Sobkowiak; Bodil Lund; Gulsen Hazirolan; Margaret Sällberg Chen; Volkan Özenci (Microbiology Spectrum, 2022)
ABSTRACT Growing evidence suggests that oral infections can modify the course of systemic diseases. To date, epidemiological data on microbial oral infections are scarce. Here, we performed a comprehensive analysis of the trend and microbial diversity in oral infection specimens referred for clinical microbiology analysis from 2010 to 2020. The microbes were isolated by culture and were identified via matrix-assisted laser desorption ionization-time of flight mass spectrometry technology (MALDI-TOF MS) throughout the study period. A total of 1,014 referred samples from dental clinics in Stockholm County with dentoalveolar abscesses and jaw osteomyelitis being the main reason were identified. Overall, the microbial composition was dominated by Firmicutes (51%), followed by Bacteroidetes (19%), Proteobacteria (12%), and Actinobacteria (5%). At the genus level, Streptococcus spp. (36%), Prevotella spp. (18%), and Staphylococcus spp. (11%) were among the most frequently reported. Interestingly, a strong increase in trend was noted for Streptococcus anginosus, Streptococcus mitis, Streptococcus sanguinis, Eikenella corrodens, Actinomyces spp., Aggregatibacter aphrophilus, Staphylococcus epidermidis, and Granulicatella adiacens during the study time (R = 0.66 to 0.89, P < 0.05), and a minor increase was noted for Enterococcus faecalis and Klebsiella spp., whereas steady levels were noted for most of the others. The present study shows the diversity of bacteria that have been involved in dental infections during the last decade in the capital of Sweden, as well as the emerging oral microbiota trend, with clear clinical implications on the oral-systemic link. IMPORTANCE Oral diseases and associated microbes are a risk factor for systemic diseases and can change the courses of these diseases. To date, epidemiological data on microbial oral infections are scarce, and longitudinal reports are lacking. We present for the first time the microbial composition of severe oral bacterial infections determined via the MALDI-TOF mass spectrometry technique in a comprehensive study between 2010 and 2020 (11 years) in Stockholm County. The trend and microbial diversity of oral infections were analyzed on referred clinical microbiological samples and were processed by standardized protocols. Trend increase was noted for Streptococcus anginosus, Streptococcus mitis, Streptococcus sanguinis, Eikenella corrodens, Actinomyces spp., Aggregatibacter aphrophilus, Staphylococcus epidermidis, Granulicatella adiacens, Enterococcus faecalis, and Klebsiella spp. Our results provide new insights into the diversity and trend of oral microbiota that were involved in serious oral infections over the past decade in the capital of Sweden and may influence the oral-systemic link.